2002
DOI: 10.1053/rmed.2002.1347
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive positive pressure home ventilation in restrictive disorders: outcome and impact on health-related quality of life

Abstract: Noninvasive positive-pressure home ventilation (NIPPHV) improves arterial blood gases, dyspnea and health-related quality of life (HRQL) in patients with restrictive thoracic diseases. Whether these changes persist during the follow-up remains unclear. The aim of this study was to investigate the long-term effects of NIPPHV upon dyspnea, HRQL, lung function and hospitalization rate in 35 patients with kyphoscoliosis and 27 individuals with several neuromuscular disorders. So, we measured dyspnea, HRQL, lung fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
1
36
1
5
Order By: Relevance
“…Similarly, Jeppesen et al (9) showed longer survival with noninvasive ventilator support, with the 15-year postdiagnosis survival increasing from 51.7% to 76.5% and 20-year survival increasing from 41.3% to 66.6%. Positive changes in psychosocial functioning and mental well-being have been reported (6,10).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Jeppesen et al (9) showed longer survival with noninvasive ventilator support, with the 15-year postdiagnosis survival increasing from 51.7% to 76.5% and 20-year survival increasing from 41.3% to 66.6%. Positive changes in psychosocial functioning and mental well-being have been reported (6,10).…”
mentioning
confidence: 98%
“…The failure often occurs during otherwise benign upper respiratory tract infections. Bronchial mucous plugging, and progressive weakening and fatigue of inspiratory and expiratory muscles compromise the already severe pulmonary dysfunction further (3)(4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After three months of NIV in KS patients, Ellis et al [26] have found that the length and quality of REM sleep improved, while oxygenation increased and transcutaneous carbon dioxide tension decreased. After NIV, daytime arterial blood gas results improvement and hospitalisation rate decrease were observed as well [26,27]. However, NIV does not improve spirometry parameters [27].…”
Section: Treatment Of Chronic Respiratory Failure and Sleep Disordersmentioning
confidence: 91%
“…After NIV, daytime arterial blood gas results improvement and hospitalisation rate decrease were observed as well [26,27]. However, NIV does not improve spirometry parameters [27]. After termination of NIV for a few nights, patients again complained about sleepiness, breathlessness during sleep due to the results of the tests, which were inappropriate.…”
Section: Treatment Of Chronic Respiratory Failure and Sleep Disordersmentioning
confidence: 98%